Using Low-Volatility Dicamba in Dicamba-Tolerant Crops - P. Devkota; J. A. Ferrell (EDIS)
In December 2020, the herbicide labels for three products containing newer dicamba formulations (XtendiMax, Engenia, and Tavium) were updated. This publication is relevant to the growers and pesticide applicators who are applying newer, low- volatility formulations of dicamba herbicide products in DT crops. Written by P. Devkota and J. A. Ferrell, and published by the UF/IFAS Agronomy Department, revised March 2021.